Trends in Rural Landuse Patterns and their Effects on Wetlands- A Case study of Sironga Swamp, Nyamira District, Kenya - Mokono, M.; Ucakuwun, E. K.; Muigai, Kibe (Africa Environmental Review Journal, 2004)
Swamps in many parts of Kenya are now threatened as their potential as sources of clay for brick-making and diversion to other land uses is realized by the communities around them.The main driving factor for the diversion is population pressure on the land. In Nyamira District, Kenya, despite the plans by the District Development Committee (DDC) on the sustainable exploitation of the natural resources, especially those located within sensitive ecosystems such as the Sironga Swamp, the exploitation of these resources is inconsistent with the plans on paper. Irreversible destruction of the swamps could be stopped with implementation of the plans on paper, by the DDC, a change in attitude by individuals and institutions who now look at swamplands as commodities for commercial transaction. This could be achieved by setting swamps as conservation reserves and introducing strategies that divert attention of the communities away from encroachment on the swamps, for example, (i) increase the productivity of available land, (ii) diversify the rural economy away from land, (iii) impart to the communities the environmental significance of the swamps and involve them in determining and controlling the use of the swamplands.